2011
DOI: 10.1002/jcp.22760
|View full text |Cite
|
Sign up to set email alerts
|

Cdk9 T‐loop phosphorylation is regulated by the calcium signaling pathway

Abstract: Eukaryotic RNA polymerase II transcriptional elongation is a tightly regulated process and is dependent upon positive transcription elongation factor-b (P-TEFb). The core P-TEFb complex is composed of Cdk9 and Cyclin T and is essential for the expression of most protein coding genes. Cdk9 kinase function is dependent upon phosphorylation of Thr186 in its T-loop. In this study, we examined kinases and signaling pathways that influence Cdk9 T-loop phosphorylation. Using an RNAi screen in HeLa cells, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 59 publications
3
42
0
Order By: Relevance
“…Upon the activation of these naïve cells, both Cyclin T1 and pCDK9 levels increase significantly. This is likely in response to extracellular cues such as Ca ϩ2 signaling, which, as we have shown previously, plays a part in CDK9 T-loop phosphorylation following the activation of resting CD4 ϩ T cells (45). Besides the increased availability of catalytically active P-TEFb, activation of CD4 ϩ T cells also increases the availability of other host cofactors, such as NF-B, thereby creating a more favorable environment for HIV-1 transcription (46).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Upon the activation of these naïve cells, both Cyclin T1 and pCDK9 levels increase significantly. This is likely in response to extracellular cues such as Ca ϩ2 signaling, which, as we have shown previously, plays a part in CDK9 T-loop phosphorylation following the activation of resting CD4 ϩ T cells (45). Besides the increased availability of catalytically active P-TEFb, activation of CD4 ϩ T cells also increases the availability of other host cofactors, such as NF-B, thereby creating a more favorable environment for HIV-1 transcription (46).…”
Section: Discussionmentioning
confidence: 65%
“…The stability of total CDK9 protein is also dependent on T-loop phosphorylation, as we have previously shown that perturbation of T-loop phosphorylation affects total CDK9 levels (45). However, CDK9 T-loop phosphorylation does not affect Cyclin T1 protein stability.…”
Section: Fig 6 In Resting Cd4mentioning
confidence: 86%
“…CDK9 phosphorylation at the conserved T-loop residue Thr186 is inducible in quiescent CD4 + T lymphocytes, but is found to be constitutive in actively replicating T cell lines and expanding, fully activated, T cells (34)(35)(36)62,63). Consistent with molecular dynamics simulations, cell-based mutagenesis experiments demonstrated that the assembly of P-TEFb in T cells is critically dependent on the stabilization of the CDK9/CycT1 interface by phosphorylation of CDK9 at Thr186.…”
Section: Formation Of the Heterodimer Interface Between Cdk9 And Cyctmentioning
confidence: 63%
“…As mentioned previously, the CDK9 phosphorylation at Thr186 is required to sequester P-TEFb into 7SK snRNP [49, 50]. However, the same Thr186 phosphorylation is required during Tat-dependent transactivation [78, 79]. This led to the postulate that P-TEFb phosphorylated at Thr186, while inhibited by HEXIM1 on 7SK snRNP complex, is in a pre-activated state to facilitate a rapid transition to transcription elongation upon activation [49, 51, 65].…”
Section: Early Events In Tat-mediated Hiv-1 Transcriptionmentioning
confidence: 99%